Applying the blockchain technology to promote the development of distributed photovoltaic in China. (22nd January 2018) - Hou, Jianchao; Wang, Haicheng; Liu, Pingkuo
Summary: Access to energy has increasingly been provided by the Chinese Government via new alternative energy sources known as renewables in recent years. Meanwhile, the development and use of environmentally friendly renewables gradually become the basic requirements for the sustainable development in the future society. The integration of blockchain technology with distributed photovoltaic (PV) energy may break the existing pattern where the production, transportation, distribution, and sales of energy are centralized. This paper first reviews the current overall situation of China's distributed PV and further analyzes the policy environment with respect to the development of distributed PV. On the basis of the analysis of the status quo, the paper then discusses the internalities (strengths and weaknesses) and the externalities (opportunities and threats) that have driven the development of China's distributed PV by illustrating the SWOT analysis. The data structure and characteristics of blockchain are analyzed to identify the application mode of blockchain technology in the distributed PV industry for the first time. Through our research, some conclusions and policy proposals are finally put forward to provide support to the formulation of related policy in the Chinese Government and industry association. Abstract : Highlights Current situation of China's distributed photovoltaic is investigated. Policy environment is presented and analyzed. Strengths, weaknesses, opportunities, and threats are illustrated and classified. How blockchain technology can promote the development of distributed photovoltaic is studied for the first time. The suggestion on promoting the development of blockchain is proposed.